The pain ratio before and after the application of physiotherapy for dysfunction of temporomandibular joint - Lejla Hadžić; Peter Heidemann; Samir Bojičić; Namik Trtak; Eldad Kaljić; Amra Mačak Hadžiomerović (Journal of Health Sciences)
Introduction: Physiotherapy, a non-invasive method of conservative treatment, that includes manual therapy, exercises and physical procedures, is used in the treatment of temporomandibular dysfunction and polyarticular laxity. It has been proven that physiotherapy focused on temporomandibular dysfunction is an essential element of treatment that leads to a reduction in pain, an improvement in temporomandibular joint (TMJ) function, and an improvement in quality of life. Physiotherapy treatment aims to alleviate the symptoms and try to restore the normal function of the masticatory system, for which various techniques can be used. The aim of the study was to determine the type, intensity, and frequency of TMJ dysfunction pain before and after physiotherapy.